Geochemistry and petrogenesis of mesoproterozoic dykes of the irkutsk promontory, southern part of the Siberian Craton - Donskaya, T.; Gladkochub, D.; Ernst, R.; Pisarevskiy, Sergei; Mazukabzov, A.; Demonterova, E. (M D P I AG, 2018)
We present new geochemical and Nd isotopic data on two Mesoproterozoic Listvyanka (1350 ± 6 Ma) and Goloustnaya (1338 ± 3 Ma) mafic dyke swarms located in the Irkutsk Promontory of the southern part of the Siberian craton. Listvyanka dykes are sub-vertical with NNE trend, while Goloustnaya dykes are characterized by prevailing W trend. Listvyanka and Goloustnaya dykes are composed of medium to coarse grained dolerites. All dolerites correspond to sub-alkaline tholeiitic basalts according to their major-element compositions with lower to moderate mg#, varying from 36 to 54. The trace and rare earth element abundances in Listvyanka and Goloustnaya dolerites are generally close to basalts of the oceanic island basalts (OIB) type. The Listvyanka dolerites demonstrate slightly positive eNd(t) values varying from +1.1 to +1.5, while the Goloustnaya dolerites are characterized by lower eNd(t) values ranging from -0.9 to +0.1. Geochemical and isotopic affinities of the Listvyanka dolerites suggest their enrichment by a mantle plume related source. For the Goloustnaya dolerites, we assume also some additional lithospheric input to their mantle plume-related source. The emplacement of both studied dolerites took place in intracontinental extensional setting, caused by a single rising mantle plume. Listvyanka and Goloustnaya dolerites are coeval to several mafic magmatic events in northern Laurentia and likely represent part of the Mesoproterozoic plumbing system of a Siberian–Laurentian Large Igneous Province.